Modernização da agroindústria açucareira na Paraíba: o caso da Usina Santa Maria - Cabral, Caterine Soffiati (2022)
From 1890 onwards, the replacement of traditional mills by modern sugar factories, the mills, began in the Brazilian Northeast. In 1931, in the municipality of Areia, located in the Brejo region of Paraíba, the Usina Santa Maria was built, having as its first owner Francisco de Assis P. de Mello and his family who commanded the plant until 1952, when it was sold to Solon Lira. Lins, who remained at the plant until its bankruptcy in the 1990s. The present master's dissertation has the general objective of understanding the meanings of the practices of these two mill owners, with emphasis on the period of modernization and territorial expansion of the plant, which took place through the programs of the Instituto of Sugar and Alcohol (IAA) and especially after the National Alcohol Program (Proálcool). To this end, we analyzed the genealogies of these families and their social conditions and reconstructed part of the history of Usina Santa Maria, through field research and archival research with the Documental Collection of Usina Santa Maria. The preliminary results of the research point to the importance of the role of the State in the process of modernization of the plant, and the presence of mismatches between the plant owner's habitus and the requirements of the economic structure.